The billy goats gruff - Bingham Jane (USBorne china, 2009)
The Billy Goats Gruff is a classic Norwegian fairy tale about three goats who need to cross a bridge to reach a lush meadow for food. However, the bridge is guarded by a fearsome troll who threatens to eat anyone who tries to cross. The goats, ranging from small to large, cleverly outwit the troll by taking turns crossing, with each goat promising the next one will be a better meal. When the largest goat finally crosses, he confronts and defeats the troll, allowing all three goats to safely enjoy the meadow. The tale highlights themes of cleverness, bravery, and teamwork.